2021
DOI: 10.2147/opth.s318317
|View full text |Cite
|
Sign up to set email alerts
|

Epithelium-on Corneal Collagen Cross-Linking with Hypotonic Riboflavin Solution in Progressive Keratoconus

Abstract: Introduction: Epithelium-off cross-linking (epi-off CXL) has long been established as the gold standard treatment for progressive keratoconus. Several protocols for epithelium-on (epi-on) CXL have been proposed to help reduce post-operative pain and facilitate visual recovery, but there is no epi-on treatment approach that is currently approved in the United States. The hydrophilic and macromolecular characteristics of conventional epi-off riboflavin formulations may create clinical challenges for absorption t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…12,13 Clinical modifications such as benzalkonium chloride and other permeability enhancers, hypo-osmolar riboflavin solutions, and substituting conventional dextran viscosity agents with hydroxypropylmethyl cellulose, among others, may reduce this resistance to riboflavin molecules, improve UV-A diffusion, and consequently augment the efficacy of epi-on CXL. 12,[14][15][16][17] According to a recent meta-analysis by D'Oria et al, epion CXL techniques (without oxygen supplementation) have similar efficacy in halting the progression of KC as epioff CXL techniques as well as visual, topographic, endothelial, and pachymetry parameters; however, epi-on CXL has added benefits such as increasing comfort and less epithelial healing-related complications. 18 A few studies have mentioned the incidence of diffuse punctate keratitis after epi-on CXL, which might require application of a soft contact lens for a few days, hence undermining the added benefit of epithelial preservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Clinical modifications such as benzalkonium chloride and other permeability enhancers, hypo-osmolar riboflavin solutions, and substituting conventional dextran viscosity agents with hydroxypropylmethyl cellulose, among others, may reduce this resistance to riboflavin molecules, improve UV-A diffusion, and consequently augment the efficacy of epi-on CXL. 12,[14][15][16][17] According to a recent meta-analysis by D'Oria et al, epion CXL techniques (without oxygen supplementation) have similar efficacy in halting the progression of KC as epioff CXL techniques as well as visual, topographic, endothelial, and pachymetry parameters; however, epi-on CXL has added benefits such as increasing comfort and less epithelial healing-related complications. 18 A few studies have mentioned the incidence of diffuse punctate keratitis after epi-on CXL, which might require application of a soft contact lens for a few days, hence undermining the added benefit of epithelial preservation.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Clinical modifications such as benzalkonium chloride and other permeability enhancers, hypo-osmolar riboflavin solutions, and substituting conventional dextran viscosity agents with hydroxypropylmethyl cellulose, among others, may reduce this resistance to riboflavin molecules, improve UV-A diffusion, and consequently augment the efficacy of epi-on CXL. 12,14–17…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, using BAC permeability enhancer, hypo-osmolar riboflavin solutions, substituting conventional Dextran ophthalmic viscosity agent agent with HPMC, removing the mucin tear layer from the epithelial surface with a sterile sponge, and rinsing away excess riboflavin solution on the corneal surface prior to UV-A irradiation have been shown to improve epion CXL outcomes. 16,[18][19][20]26 Despite these epi-on CXL procedural modifications, a recent meta-analysis review still indicated reduced efficacy with epi-on CXL when compared with the conventional epi-off CXL. 32 In another study, retreatment was required in one third of the study eyes treated with the epi-on procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Riboflavin corneal absorption was not confirmed during this study but was assumed based on previous studies. 26,27…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation